Sexual experiences of girls engaged in child marriage: A review of qualitative - Kamilah, Farhah; Rosa, Elyse Maria (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Child marriage cases appear to occur in children between 15 and 18 years of age. Girls who are forced into marriage show fear of having sex with their husbands because they are foreign to this situation. Previous research has shown that child marriage causes trauma to girls due to forced sexual intercourse. This study aims to explore sexual aspects from the perspective of married girls. This study uses 3 databases PubMed, EbscoHost, and Proquest. The main keywords are "child marriage", "early marriage", "Sexual", "Experience", and "Qualitative". The search for articles was carried out in accordance with the guidelines of PRISMA. The findings were 5 main themes from 15 articles. The findings are the desire to have children soon after marriage, delay of having children, husband and wife relationship in child marriage, lack of knowledge related to reproductive health, and powerlessness makes reproductive health decisions. The problem of the sexual aspect of child marriage makes it difficult for girls to live their married lives. Girls must quickly adapt to their role as wives and be able to meet everyone's marriage expectations in general. However, another case also explains that families and partners understand the condition of girls who are not ready to face this phase. The views of society and families build perceptions of child marriage, including the fulfillment of sexual needs therein.